2015
DOI: 10.1016/j.compmedimag.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven approach to prostate cancer detection from dynamic contrast enhanced MRI

Abstract: Magnetic resonance imaging (MRI), particularly dynamic contrast enhanced (DCE) imaging, has shown great potential in prostate cancer diagnosis and staging. In the current practice of DCE-MRI, diagnosis is based on quantitative parameters extracted from the series of T1-weighted images acquired after the injection of a contrast agent. To calculate these parameters, a pharmacokinetic model is fitted to the T1-weighted intensities. Most models make simplistic assumptions about the perfusion process. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Before extracting the features from the TIC in the DCE-MRI images, we performed the normalization as [8]T1irealt=intipreipre,where i real ( t ) denotes the final normalized TIC, i n ( t ) denotes the original TIC, and i (pre) denotes the average intensity in the first eight scans (before the injection of contrast agent) of i n ( t ).…”
Section: Methodsmentioning
confidence: 99%
“…Before extracting the features from the TIC in the DCE-MRI images, we performed the normalization as [8]T1irealt=intipreipre,where i real ( t ) denotes the final normalized TIC, i n ( t ) denotes the original TIC, and i (pre) denotes the average intensity in the first eight scans (before the injection of contrast agent) of i n ( t ).…”
Section: Methodsmentioning
confidence: 99%
“…We used the apparent diffusion coefficient (ADC) from diffusion MRI, and three pharmacokinetic parameters from DCE MRI: volume transfer constant, k trans , fractional volume of extravascular extracellular space, v e , and fractional plasma volume v p [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have used feature selection techniques for the purpose of unraveling the most efficacious subset of high-dimensional MR feature sets. However, in a recent study on prostate cancer diagnostic performance, Haq et al applied the lasso method to find the optimal set of principal components from T1 intensities and semiquantitative DCE-MRI features, and found that the set produced by the lasso method outperformed traditional pharmacokinetic parameters in receiver operating characteristic tests of diagnostic performance [51] . Based on our literature review, there seems to be no previous studies that combine the lasso method with data imputation in the repetitive manner for statistical evaluation, as done by us.…”
Section: Discussionmentioning
confidence: 99%